Development of Web Application Functionality for the Driver Management System at Katadata - Dimas Raharjo; Bagir, Muhammad (Faktor Exacta, 2026)
Katadata’s Driver Management System (DMS) previously facilitated structured driver and vehicle scheduling; however, it exhibited limitations in functionality, scheduling flexibility, and user interface design. This study aimed to analyze the existing system and develop an enhanced DMS to improve operational efficiency and usability. System requirements were identified using the PIECES framework, while the development process followed the Waterfall software development model. Several new features were implemented, including WhatsApp-based notifications, interactive maps for multipurpose operational support, enhanced scheduling based on location, fuel consumption, and vehicle status, as well as a driver performance evaluation module. Functional validation was conducted using Black Box testing to verify that all implemented features satisfied both functional and non-functional requirements without affecting the stability of the existing system. The results demonstrate that the enhanced DMS improves scheduling flexibility, increases the accuracy and accessibility of operational data, and provides more comprehensive information to support decision-making. Furthermore, the utilization of open-source libraries contributed to reducing development costs while maintaining system performance and scalability.